GROWTH RESPONSE OF NANNOCHLOROPSIS AT OUTDOOR CULTIVATION IN MEDIUM WITH VARIATION OF NITROGEN CONCENTRATION - Astuti, J. Tri; Sriwuryandari, Lies; Yusiasih, Retno; Sembiring, Tarzan (Teknologi Indonesia, 2010)
Micro-algae are fast-growing unicellular photosynthetic microorganisms that able to fi x CO2 while capturing solar energy. Source and concentration of nitrogen itself affected to the growth character and composition of microalgae. Cultivation with limited of nitrogen resulted great increase in the lipid content. This study was conducted to investigate the infl uence of nitrogen concentration to the growth rate and lipid characteristics of Nannochloropsis sp. In this study, ammonium nitrate (NH4NO3) was added in different concentration, i.e. 0; 30; 70; and 100% based on nitrogen content in f/2 medium, or equivalent to 0; 1.06; 2.47; and 3.53 (10-4 M). All treatment was prepared triplicate, then cultivated at outdoor batch culture systems and aerated continuously with a sterilized of atmospheric air. The algae biomass was harvested at 14th day after inoculated and then analyzed. Data showed that Nannochloropsis sp. could be cultivated in the outdoor batch system, which temperature was in the range of 26.1137.97oC, with average of 33.44oC. Compared to its initial condition, pH culture increased signifi cantly from 6.92 to 8.54. The highest OD680nm (0.500) and dry cell concentration (458mg.L-1) was obtained by using NH4NO3 at 2.47x10-4 M. The lipid content was 63.58% and 46.59% of dry cell weight when using nitrogen 1.06x 10-4M and 2.47x10-4M, respectively. Composition of fatty acid was not signifi cantly affected by the changing of nitrogen concentration. Palmitic acid (C16:0) was the most of fatty acid in Nannochloropsis sp. (44.4753.97%), followed by lauric acid (25.7834.34%), and myrictic acid (19.0721.19%). The using of N-NH4NO3 at 2.47x10-4M gave the highest lipid content of 213.15mg.L-1.